2018
DOI: 10.3390/e20040303
|View full text |Cite
|
Sign up to set email alerts
|

The Conservation of Average Entropy Production Rate in a Model of Signal Transduction: Information Thermodynamics Based on the Fluctuation Theorem

Abstract: Cell signal transduction is a non-equilibrium process characterized by the reaction cascade. This study aims to quantify and compare signal transduction cascades using a model of signal transduction. The signal duration was found to be linked to step-by-step transition probability, which was determined using information theory. By applying the fluctuation theorem for reversible signal steps, the transition probability was described using the average entropy production rate. Specifically, when the signal event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 50 publications
(129 reference statements)
2
16
0
Order By: Relevance
“…Finally, a pre-stimulation steady state of the individual step is recovered. Such reaction chain schemes were previously described by Gaspard et al and Tsuruyama [17,18,[28][29][30].…”
Section: A Common Brc Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, a pre-stimulation steady state of the individual step is recovered. Such reaction chain schemes were previously described by Gaspard et al and Tsuruyama [17,18,[28][29][30].…”
Section: A Common Brc Modelmentioning
confidence: 99%
“…Recent studies showed that the BRC can be interpreted as a binary code system with two forms of signalling molecules, namely an active form (X j *) and an inactive form (X j ) in individual step [18][19][20]. The total signal event number Ψ in a given BRC event, can be described using the concentration of inactive X j and active molecules X j * as follows:…”
Section: Binary Code Model Of Brcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, considering specific reaction kinetics and thermodynamic analysis in individual reactions, there have been few studies discussing signal transduction, for example, limited to chemotaxis models of Escherichia coli [7], and several theoretical researches about mitogen-activated protein kinase (MAPK) cascade and bistability or ultra-sensitivity and feedback controllability of the cascade have been reported [8][9][10][11][12][13]. In addition, information thermodynamics of MAPK cascade has been recently reported [14][15][16]. This article reviews these recent studies from information thermodynamics in relation to fluctuation theorem.…”
Section: Introductionmentioning
confidence: 99%